Synthesis and biological evaluation of selective phosphonate-bearing 1, 2, 3-triazole-linked sialyltransferase inhibitors. Issue 10 (29th June 2021) - Dobie, Christopher; Montgomery, Andrew P.; Szabo, Rémi; Yu, Haibo; Skropeta, Danielle
Abstract : Key modifications of previous sialyltransferase inhibitors increased their activity against hST6Gal I and has further implications for synthetically accessible ST inhibitor design. Abstract : The critical role of sialyltransferase (ST) enzymes in tumour cell growth and metastasis, as well as links to multi-drug and radiation resistance, has seen STs emerge as a target for potential antimetastatic cancer treatments. One promising class of ST inhibitors that improve upon the pharmacokinetic issues of previous inhibitors is the 1, 2, 3-triazole-linked transition-state analogues. Herein, we present the design and synthesis of a new generation of 1, 2, 3-triazole-linked sialyltransferase inhibitors, along with their biological evaluation demonstrating increased potency for phosphonate bearing compounds. The six most promising inhibitors presented in this work exhibited a greater number of binding modes for hST6Gal I over hST3Gal I, with K i ranging from 3–55 μM. This work highlights phosphonate bearing triazole-linked compounds as a promising class of synthetically accessible ST inhibitors that warrant further investigation.